Theoretical and legal issues of the European Union outspread: present state and possibilities - Теремцова, Ніна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
An author describes an urgent issue, which are devoted to European Union, its outspread, also raised theissue of present state and possibilities.